Analisis Aliran Daya Pada Sistem Stand Alone Pembangkit Listrik Tenaga Mikro Hidro (PLTMH) Al Hanan Dengan Metode Newton Rhapson - Herawati, Afriyastuti; Putra, Ripo Utama; Handayani, Yanolanda Suzantry; Anggraini, Ika Novia (UNIB Press, 2022)
Analysis of power flow in the power system is used to determine the parameters of the system itself. The benefit of the power flow analysis is to determine whether the amount of power in the electric power system still meets the predetermined limits, as well as to determine the number of existing losses, and to obtain the initial conditions for planning the new system. To solve the power flow problem, a power flow simulation can be performed using ETAP software. Simulations were carried out using the Newton-Rhapson method to determine the flow of power during the rainy and dry seasons. The results of the power flow simulation in the rainy season show that the highest active and reactive power values ​​are found in bus 1, namely 156.78 kW and 101.77 kVAR, while the simulation during the rainy season shows the highest active power and reactive power in bus 1, which is 137.85 kW and 88.97 kVAR. Then the highest voltage drop in the rainy season is 3.11% and the dry season is 2.78%. The Newton-Rhapson method requires 2 iterations to reach a convergent value.